ADAPTATION OF THE FAMILY HARDINESS INDEX (FHI) INSTRUMENT FOR INDONESIAN ADOLESCENTS: Alat Ukur Family Hardiness Index (FHI) untuk Remaja Indonesia - Erica, Luisa; Pudjiati, Sri Redatin Retno (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Family resilience in adolescence measures the ability to cope with challenges and disruptions within the family and engage in positive adaptation in their role as children. To address the limitations of the availability of family resilience measurement tools in the Indonesian language, this study aims to adapt and test the reliability and validity among adolescents. One widely used measurement tool for assessing family resilience internationally is the Family Hardiness Index (FHI), developed as part of The Resilience, Adaptation, and Well-Being Project. The testing was conducted on 276 participants aged 12–17 years (M = 14.5; SD = 1.7), with a gender distribution of 124 males (45%) and 152 females (65%). Psychometric property testing revealed that this adapted instrument met reliability criteria with a Cronbach's alpha value of 0.75 and fulfilled construct validity criteria using confirmatory factor analysis. Through these findings, it is hoped that research related to family resilience for Indonesian adolescents will continue to advance, particularly among families facing various challenges and disruptions. Additionally, multiple suggestions and implications arising from this adaptation are discussed in the concluding section of this article.